An integrated engineering worldview of synthetic biology education through the lens of webinar based pedagogy - George, Iain; Ross, Paul; Yang, Yixian; Holub, Martin; Rajpurohit, Nina; Aldulijan, Ibrahim; Beal, Jacob; Vignoni, Alejandro; Mishler, Dennis (Frontiers in Bioengineering and Biotechnology, 2024)
Synthetic biology is an interdisciplinary field that brings together engineering and biology concepts alongside the arts and social sciences to develop solutions to pressing problems in our world. The education of students entering this field has relied on a diverse set of pedagogical methods to accomplish this goal. One non-profit group, iGEM -the International Genetically Engineered Machine competition, has been a driver of students' awareness of synthetic biology for the last 20 years giving many young researchers their first experience in the field of synthetic biology.Dissemination of synthetic biology concepts by iGEM has occurred through several programs including a webinar series started during the 2020 COVID pandemic. The iGEM webinar series successfully engaged students by taking inspiration from synthetic biology programs in Europe, North America, and Asia that had themselves evolved alongside iGEM. The webinar designers modeled the content after their experiences in iGEM as well as their academic courses, pedagogy, and mentoring experiences. This series has produced globally accessible pedagogy for both technical synthetic biology knowledge and the communication skills necessary to build and communicate synthetic biology projects. The hope is that this series functions as a lasting blueprint that can be used by future educators in synthetic biology and other disciplines to reduce barriers that students face when attempting to enter cutting edge fields.